Fiscal Policy From the Perspective of Human Rights and Justice - Palomeque Cruz, Leticia (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
Today, fiscal policy is analyzed from the perspectives of gender equity, the fight against informality, the protection of domestic and unpaid work; where the increase in spending, both in subsidies and transfers, is key to combating the social and economic effects of the pandemic. It is essential to increase tax collection progressively to maintain an expansive fiscal policy; control tax evasion and avoidance and illicit financial flows. Fiscal policy has an important impact on welfare, it is reflected in the income of the population and the taxes they directly or indirectly pay. In addition, taxation is the main source of financing public spending, which allows the construction of public works and social programs.